Optimasi Fraksi Volume Komposit Serat Kersen Terhadap Kekuatan Tarik - Tri Hartutuk Ningsih; Deni Hardiansyah Tangahu; Defi Tri Wahyudi (Fakultas Teknik UMSU, 2019)
Composite is a material formed from a combination of two or more forming materials through a mixture that is not homogeneous. Composites have properties such as corrosion resistance, light weight, faster assembly, and are able to compete with metals by not losing the characteristics and strength of the mechanism. This research was conducted to develop composite materials with more specific properties, one of which is the use of natural fibers as reinforcing raw materials in composites. This research uses the epidermal skin fiber with the epoxy matrix and is applied to the crossbow as a new environmentally friendly composite material and supports the idea of utilizing grained fiber into products that have high economic and technological qualities. This research was carried out by varying the fiber volume fraction of 40%, 50%, 60%, and 70%. In this study tensile test specimens using ASTM D 638 standard. To determine the physical properties, experiments were conducted to calculate density and measurement of fiber diameter. From this study the tensile strength value of the 70% volume fraction is 70.30 MPa The test results show that the composite material of the kersen fibers has increased strength as the fiber volume fraction increases